Estimation of dark and active dielectric constants in the sub-THz frequency domain of an optically tunable organic semiconductor blend of poly(3-hexylthiophene) and phenyl-C61-butyric acid methyl ester. (1st May 2018) - Andy, Andre S.; Kneller, James W. E.; Sushko, Oleksandr; Dubrovka, Rostyslav; Parini, Clive; Scott, Ken; Kreouzis, Theo; Donnan, Robert S.
Abstract: The dielectric properties of a 95% poly(3-hexylthiophene):5% phenyl-C61-butyric acid methyl ester blend are measured in the dark and under white light illumination by quasi-optical transmissometry and terahertz time-domain spectroscopy. The real part of the dielectric constant varies monotonically between 2.75 and 3.50, in agreement with the literature, and displays a reversible photoinduced drop of 0.05–0.55 at sub-THz. The imaginary part fluctuates between 0.1 and 1.5 in the dark and displays a reversible increase upon illumination of 0.10–0.52 at sub-THz. The corresponding charge carrier concentration under illumination (using transient and steady-state photoconduction) is 10 14 to 10 15 cm −3 .